2021
DOI: 10.3389/fpsyg.2021.571257
|View full text |Cite
|
Sign up to set email alerts
|

Italian Community Psychology in the COVID-19 Pandemic: Shared Feelings and Thoughts in the Storytelling of University Students

Abstract: This study investigated how young Italian people experienced the period of peak spread of COVID-19 in their country by probing their emotions, thoughts, events, and actions related to interpersonal and community bonds. This approach to the pandemic will highlight social dimensions that characterized contextual interactions from the specific perspective of Community Psychology. The aim was to investigate young people's experiences because they are the most fragile group due to their difficulty staying home and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 87 publications
1
21
0
1
Order By: Relevance
“…Anxious emotions took over and the community dimensions took on more specific and coordinated forms, less impromptu, and community was mostly considered a problem by individuals. As stated in other contributions (Di Napoli et al, 2021 ; Migliorini et al, 2021 ) in the first phase of emergency, strong feelings of fear (Pulcini, 2001 ), together with the awareness of being united with other human beings as well as intense perception of vulnerability and weakness, induced people to renew the desire for bonding, generating and reinvigorating their desire for community (Marta, Marzana, Aresi, & Pozzi, 2016 ). In the following phase, the drive for sociality and solidarity was more ambiguous, and the personal behavioural responses were more varied, also due to anxiety.…”
Section: Discussionmentioning
confidence: 89%
“…Anxious emotions took over and the community dimensions took on more specific and coordinated forms, less impromptu, and community was mostly considered a problem by individuals. As stated in other contributions (Di Napoli et al, 2021 ; Migliorini et al, 2021 ) in the first phase of emergency, strong feelings of fear (Pulcini, 2001 ), together with the awareness of being united with other human beings as well as intense perception of vulnerability and weakness, induced people to renew the desire for bonding, generating and reinvigorating their desire for community (Marta, Marzana, Aresi, & Pozzi, 2016 ). In the following phase, the drive for sociality and solidarity was more ambiguous, and the personal behavioural responses were more varied, also due to anxiety.…”
Section: Discussionmentioning
confidence: 89%
“…Feelings of psychological distress that accompany perceptions of unfulfilled societal expectations (Culatta & Clay-Warner, 2021) may have thus been diminished or absent. And indeed, feelings of solidarity and community may have been heightened (Di Napoli et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…One of the factors of prosocial behavior and caring for others in a crisis is the emerging sense of common identity and collectivism, which stem from a common experience of being in straitened circumstances (Drury et al, 2009 ; Cruwys et al, 2020 ; McKinley, 2020 ). Di Napoli et al ( 2021 ) and Politi et al ( 2021 ) found that prosocial attitudes during the COVID-2019 pandemic are driven by collective values and solidarity. Developing a sense of loyalty can help coordinate threat management efforts (Haslam and Reicher, 2006 ) and promote group commitment and social norms (Ellemers et al, 2002 ; Neighbors et al, 2010 ; Stevens et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%